Effect of singing interventions on symptoms of postnatal depression: three-arm randomised controlled trial. (9th January 2018) - Fancourt, D.; Perkins, R.
Summary: This study assessed whether a novel psychosocial intervention could reduce symptoms of postnatal depression (PND) in the first 40 weeks post-birth. Analyses were carried out of 134 mothers with symptoms of PND randomised into 10 weeks of group singing workshops or group play workshops for them and their babies, or usual care (trial registration: NCT02526407). Overall, among all mothers with symptoms of PND, there was a non-significant faster improvement in symptoms in the singing group ( F 4, 262 = 1.66, P = 0.16, η 2 = 0.012). When isolating mothers with moderate–severe symptoms of PND, this result became significant, with a faster improvement in symptoms in the singing group ( F 3.9, 139.8 = 2.74, P = 0.033, η 2 = 0.028). Declaration of interest: None.